Facile synthesis of bio-based latent curing agent and its high-Tg epoxy network. (5th February 2022) - Yu, Zhen; Ma, Songqi; Liu, Yanlin; Su, Yi; Feng, Hongzhi; Li, Pengyun; Dong, Yunxiao; Tang, Zhaobin; Zhang, Kewei; Zhu, Jin
Graphical abstract: Highlights: A bio-based latent curing agent with phytic acid salt was successfully synthesized. One-component epoxy system had excellent storage stability and curing activity. The cured epoxy resins possessed high glass transition temperature of ∼205 °C. Abstract: Developing latent curing agents from bioresources are of great significance to the sustainable development of epoxy resins. In this work, a bio-based latent curing agent–phytate salt PAIM–was prepared by a simple salt-forming reaction between imidazole and naturally occurring phytic acid, and was mixed with commercial bisphenol A epoxy to obtain one-component epoxy system. The system exhibited excellent storage stability at storage temperature and high curing reactivity at curing temperature. Since phytic acid possesses twelve hydroxyl groups that can react with epoxy groups, the cross-link density of the resin can be increased, as a result, T g of the cured one-component epoxy reached up to 205 °C. Thermal stability and degradation process of the cured epoxy were investigated by thermal gravimetry-infrared analysis. Due to the introduction of phytic acid, residual carbon of resins increased and the gas release rate decreased. This latent curing agent with facile synthesis, environmental protection and biomass origin is in line with the current development trend and has great industrial application value.